2022
DOI: 10.5812/tms-129037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Virulence Genes and Antibiotic Resistance of Methicillin-resistant Staphylococcus aureus (MRSA) and Methicillin-susceptible Staphylococcus aureus (MSSA) Isolates in Intensive Care Unit (ICU) and Non-ICU Wards

Abstract: Background: We are witnessing the increasing use of antibiotics and the upward trend of resistant nosocomial infections. Therefore, identifying pathogens and determining the local patterns of antibiotic resistance are the health system's priorities in any region. Objectives: The current study aimed to investigate the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in the Intensive Care Unit (ICU) and Non-ICU wards, the toxic shock syndrome toxin-1 (TSST-1), alpha-toxin (Hla), and pantone-valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This was associated with more capillary lung lesions and bilateral disease, which required more prolonged treatment [125]. Also, more than half of S. aureus strains tested were MDR, showing resistance to fluoroquinolones [126][127][128]. Efforts have been made to improve the fluoroquinolones' potency, for example, by conjugate biofilm formation, a major virulence factor of Pseudomonas auroginosa that causes antibiotic resistance [129].…”
Section: Toxicity Study Of Nsaids and Fluoroquinolones Multi-componen...mentioning
confidence: 99%
“…This was associated with more capillary lung lesions and bilateral disease, which required more prolonged treatment [125]. Also, more than half of S. aureus strains tested were MDR, showing resistance to fluoroquinolones [126][127][128]. Efforts have been made to improve the fluoroquinolones' potency, for example, by conjugate biofilm formation, a major virulence factor of Pseudomonas auroginosa that causes antibiotic resistance [129].…”
Section: Toxicity Study Of Nsaids and Fluoroquinolones Multi-componen...mentioning
confidence: 99%
“…In a recent study in a hospital in Dezful, Iran, of 186 Staphylococcus aureus strains isolated from various specimens, 27.4% were methicillin-resistant Staphylococcus aureus (MRSA), with a 26.8% rate in the ICU. [ 17 ] Updated data is crucial to physicians and infection control committees for treatment and preventive programmes. In this study, we have retrospectively analysed and reported the epidemiological and antimicrobial susceptibility profiles of BSI patients during the past four years in AL Zahra Hospital, Isfahan, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] MRSA is highly resistant to cefoxitin, ciprofloxacin, gentamicin, and other antibiotics. 4,5 The most commonly used treatments for MRSA infection include radiation, 6 antibiotic, 7,8 surfactant molecular, 9 and nanomaterial 10 therapies; among these, antibiotic therapy is the first choice in many cases. However, antibiotic resistance remains one of the leading causes of death worldwide.…”
Section: Introductionmentioning
confidence: 99%